Social being and the Navan complex: c.4000BC-c.90BC - Price, D (2015)
Archaeological records at the Navan site are fragmented and difficult to interpret. This site, in County Armagh, Northern Ireland, features artefacts extending over 4,000 years from the Neolithic period to the Iron Age. This thesis provides a framework for understanding this important material culture. Through an analysis of archaeological theories and specific physical items, links are established among the natural world, culture, and the Navan residents’ understanding of the cosmos. This analysis covers the landscape (e.g. topography), constructed objects (e.g. prehistoric infrastructure such as pools, roads and earthworks), and metaphysical concepts (e.g. sound and time), thus building a holistic picture of how these settlers might have viewed themselves, the physical world around them, and the spiritual world they imagined. While it is not possible to determine definitively these groups’ purposes and motives, the thesis finds clues in the incoherentarchaeological evidence. It explores possible functions for archaeological markers whose significance is not clear.These markers could, for instance, have beenmeans of social separation orceremonial signifiers. Therefore the thesis is both an analysis of a particular site and an investigation into how the archaeological process itself, specifically in a situation of challenging evidence, enables distant worlds to be understood.